TROWULAN KOTA TERAKOTA - Prima Yustana (Ornamen, 2011)
Geographical conditions of Trowulan are very supportive available raw clay, then logically the findings of artifacts found in the Trowulan madeÂ from raw clay or is often called terracotta. Trowulan has a carrying capacity as a prosperous city and a center of government in antiquity according to archaeologists, also the capital of the kingdom of Majapahit. Many of the findings in the form of artifacts that confirm the existence of Trowulan as a community center, in the form of buildings and objects supporting household activities, such as jars, piggy bank, well, wuwungan, and various sculptures as toys and decorative objects.TrowulanÂ as terracotta city still keeps the mysteries of interest to the scientists or researchers to dig deeper into its existence as a witness to the history of Indonesia. Indonesia trip many people motivated by the existence of the Majapahit kingdom, the kingdom has a tremendous influence on his time, influence includes political, economic and art. Art in many predominantly in the form of Majapahit terracotta objects, terracotta supported by the mention of the many factors that strengthen its presence as a descriptions and evidence contained in the current Trowulan.